Benchmarking the effects of transcranial temporal interference stimulation (tTIS) in humans. (September 2022) - von Conta, Jill; Kasten, Florian H.; Schellhorn, Klaus; Ćurčić-Blake, Branislava; Aleman, André; Herrmann, Christoph S.
Abstract: Deep brain stimulation (DBS) provides clinical benefits for several neurological and psychiatric conditions. By overcoming the limitations and risks of conventional DBS, transcranial temporal interference stimulation (tTIS) has the potential to offer non-invasive stimulation of deep brain regions. However, research that investigates the efficacy of tTIS is limited to animal studies or computer simulations and its capability to modulate neural oscillations in humans has not been demonstrated so far. The method of tTIS is hypothesized to elicit its effects via neural entrainment, corresponding to the supposed mechanism of action underlying transcranial alternating current stimulation (tACS), another, more established non-invasive brain stimulation technique. Physiological effects of tACS are well established for cortical brain oscillations, but not for deep brain structures. In particular, aftereffects on the power of parieto-occipital alpha oscillations have been shown repeatedly. In a first attempt to test the efficacy of tTIS in the human brain, the current study thus seeks to compare the effects of tTIS to the well-studied aftereffect of tACS in the cortex. To investigate this research question, the current study compared MEG-recorded brain activity during a simple visual change detection task in 34 healthy subjects pre- and post-tTIS. Additionally, the effects of tTIS were contrasted to conventional tACS and a control stimulation. We expected that the parieto-occipital α-power will increase after tTIS and tACS, in contrast to the control stimulation. Overall, no difference between the experimental groups (tTIS, tACS and control stimulation) were found regarding the source-projected increase in α-power. Based on the results of the study two hypothesis can be made: tTIS, tACS and the control stimulation condition don't have an effect on human brain oscillations in the α-band, or, any experimental conditions of the current study can modulate brain oscillations in the α-band. Both hypotheses emphasize the importance of further studies investigating different carrier frequencies, and the comparison to sham stimulation.